Analisa Neraca Massa Pada Alat Vertical Roller Mill - Putrisya, Santi (Journal of Industrial Process and Chemical Engineering (JOICHE), 2023)
Vertical Roller Mill (VRM) is a tool usually found in the cement industry. In this tool, there are four processes, namely drying, grinding, separation, and transport. This research aims to examine the mass balance of VRM. Mass balance calculations require data on the mass of the material entered into the VRM; the data obtained is based on the material's molecular weight. The mass balance considers all the materials entering, accumulating, and leaving a system within a certain time. The mass balance calculations showed that the incoming and outgoing mass rates were the same, namely 161,797 tons/h. This result is in accordance with the provisions of the applicable law of conservation of mass